The beneficial effects of omega-3 polyunsaturated fatty acids on controlling blood pressure: An umbrella meta-analysis - Musazadeh, Vali; Kavyani, Zeynab; Naghshbandi, Behnaz; Dehghan, Parvin; Vajdi, Mahdi (Frontiers in Nutrition, 2022)
Several meta-analyses have revealed that n-3 PUFAs can lower blood pressure, but the findings are conflicting. In this regard, the present umbrella meta-analysis aimed was performed to clarify whether n-3 PUFAs have effects on blood pressure. PubMed, Scopus, Embase, Web of Science, and Google Scholar were used as international databases from inception to May 2022.To examine the effects of n-3 PUFA supplementation on blood pressure, a random-effects model was applied. The leave-one-out method was performed for the sensitivity analysis. The pooled estimate of 10 meta-analyses with 20 effect sizes revealed significant reductions in both systolic (ES = -1.19 mmHg; 95% CI: -1.76, -0.62, p<0.001) and diastolic blood pressure (ES= -0.91 mmHg, 95% CI: -1.35, -0.47; p< 0.001) following n-3 PUFAs supplementation. In studies with a sample size of ≤ 400 participants and a mean age over 45, SBP and DBP were found to be substantially reduced. Overall, this umbrella meta-analysis indicates that n-3 PUFAs supplementation might play a role in improving DBP and SBP.